1999
DOI: 10.1046/j.1365-2249.1999.00958.x
|View full text |Cite
|
Sign up to set email alerts
|

Human T lymphocyte primingin vitroby haptenated autologous dendritic cells

Abstract: Dendritic cells (DC), generated from adherent peripheral blood mononuclear cells (PBMC) by culturing with granulocyte-macrophage colony-stimulating factor (GM-CSF) and IL-4, were used to study in vitro sensitization of naive, hapten-specific T cells and to analyse cross-reactivities to related compounds. DC were hapten-derivatized with nickel sulphate (Ni) or 2-hydroxyethyl-methacrylate (HEMA), followed by tumour necrosis factor-alpha (TNF-alpha)-induced maturation, before autologous T cells and a cytokine coc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 55 publications
3
32
0
Order By: Relevance
“…In vitro T-cell activation Dai and Streilein, 1998;Rustemeyer et al, 1999;Gorbachev and Fairchild, 2001 lysine gave a prediction accuracy of 89%. The results of these investigations revealed that measurement of peptide reactivity has considerable potential utility as a screening approach for skin sensitization testing, and thereby for reducing reliance on animal-based test methods (Gerberick et al, 2007b(Gerberick et al, , 2008.…”
Section: Antigen Presentation To T H Cells and Memory T-cell Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro T-cell activation Dai and Streilein, 1998;Rustemeyer et al, 1999;Gorbachev and Fairchild, 2001 lysine gave a prediction accuracy of 89%. The results of these investigations revealed that measurement of peptide reactivity has considerable potential utility as a screening approach for skin sensitization testing, and thereby for reducing reliance on animal-based test methods (Gerberick et al, 2007b(Gerberick et al, , 2008.…”
Section: Antigen Presentation To T H Cells and Memory T-cell Generationmentioning
confidence: 99%
“…An effective system could be to expand the absolute number of antigen-specific T-lymphocytes from the naïve T-lymphocyte pool of peripheral blood samples. The system has successfully applied to determine T-lymphocyte frequencies for several allergens in human blood samples and for activation of naive hapten-specific T-lymphocytes to study the earliest T-lymphocyte and APC events in the induction of human contact hypersensitivity (Dai and Streilein, 1998;Rustemeyer et al, 1999).…”
Section: Immunogenicity Of Biologicalsmentioning
confidence: 99%
“…After in vitro induction with nickel sulfate, it was possible to stimulate quite a number of T cell clones from persons not sensitized to nickel with copper chloride. T cell clones not having received pre-treatment were not investigated (Rustemeyer et al 1999).…”
Section: Allergenic Effects 441 Skinmentioning
confidence: 99%
“…Efforts were made to study primary human T-cell responses to chemicals. Different approaches were taken to induce T-cell responses to chemicals with respect to the populations of T cells and APC used, the means of application of the test chemicals and the cell culture protocols and readouts [42][43][44][45][46][47][48][49][50][51]. Table 2 summarizes the studies that have used protocols for priming of naive T cells with chemicals applied as shown in Fig.…”
Section: Replacement Of Animal Testing: T Cells As Tools In Immunotoxmentioning
confidence: 99%
“…T cells in the presence of various cytokine cocktails [47,49]. After 10-14 days T cells were divided into three aliquots and restimulated with medium alone, with the allergen used for priming or with a noncrossreacting or crossreacting contact allergen.…”
Section: Topic 1: Chemical-reactive T Cellsmentioning
confidence: 99%